THE INFLUENCE OF CHEESE CONSUMPTION ON THE DEGREE OF ACNE VULGARIS IN STUDENTS OF MEDICINE FACULTY OF DIPONEGORO UNIVERSITY - Koncara, Fatan Khalif; Wibowo, Dhega Anindita; Riyanto, Puguh; Wikanta, Edmond Rukmana (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Introduction : Acne vulgaris is a chronic inflammatory disease of pilosebaceous follicles with a polymorphic clinical picture consisting of various skin disorders in the form of blackheads, papules, pustules, nodules, and scar tissue. Four pathogenesis underlying the emergence of AV include polysebaseal follicle hyperproliferation, excess sebum production, inflammation, and the presence of Propionibacterium acnes. The cause of this multifactorial AV, one of which is a factor of consuming fatty foods, especially saturated fat, one of the foods is cheese. Cheese is one of the foods that we usually consume as processed foods that contain lots of saturated fat. Consuming fatty foods on an irregular basis can cause acne vulgaris. Objectives : To determine the relationship of fatty food consumption with the severity of acne vulgaris in Diponegoro University Kedokeran Faculty studentsMethods : This study uses a descriptive observational design with cross sectional design in which the researcher will describe how the incidence of acne vulgaris, the severity of acne vulgaris and the factors that influence acne vulgaris, especially regarding saturated fat consumption in excess cheese in Diponegoro University Medical School students. Samples were taken by purposive sampling to produce 40 students who met the inclusion and exclusion criteria. Assessment is assessed by filling out questionnaires suffering from acne vulgaris and assessing acne vulgaris in respondents. Analysis of the data used in the study is an analysis with the Chi Square test. Result : In conclusion, clustered pimples are a dominant factor in the assessment of acne (p<0,05). Conclusion: In this study it was found that there was no significant relationship between cheese consumption with the severity of acne vulgaris and pimples arising from acne is acne that occurred before the existence of this studyKeywords : acne vulgaris, fat, cheese